2020
DOI: 10.2147/dmso.s265988
|View full text |Cite
|
Sign up to set email alerts
|

<p>Determinants of Diabetic Foot Ulcer Among Adult Patients with Diabetes Attending the Diabetic Clinic in Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia: Unmatched Case–Control Study</p>

Abstract: Background: Diabetic foot ulcer is among the commonest complications of diabetic mellitus attributed to a number of morbidity and mortality cases in diabetic patients. Nowadays, the incidence of diabetic foot ulcer is increasing due to the increased prevalence of diabetes. However, the risk factors of the problem are less studied in Ethiopia. Hence, this study was conducted to assess the determinants of diabetic foot ulcer among adult patients with diabetes attending a diabetic clinic in Tikur Anbessa Speciali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
2
9
1
Order By: Relevance
“…There are a number of risk factors associated with the development of DFU. Studies have reported that peripheral neuropathy (Abdissa, Adugna, et al, 2020 ; Adem et al, 2020 ; Mariam et al, 2017 ; Woldemariam et al, 2020 ), poor foot self‐care behaviours (Mariam et al, 2017 ; Tola et al, 2021 ; Tolossa et al, 2020 ; Woldemariam et al, 2020 ) overweight and obesity (Adem et al, 2020 ; Mariam et al, 2017 ; Tola et al, 2021 ; Tolossa et al, 2020 ), taking insulin alone (Tola et al, 2021 ; Woldemariam et al, 2020 ), rural residence (Mariam et al, 2017 ; Tolossa et al, 2020 ), delayed DM follow‐up, history of infection and hypertension (Tola et al, 2021 ), and presence of foot callus, longer duration of DM and advancing age (Tolossa et al, 2020 ) are positively associated with DFU. In addition, a studies have shown that retinopathy, nephropathy, poor glycaemic control, smoking and height are positively associated with DFU (Banik et al, 2020 ; Rossboth et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of risk factors associated with the development of DFU. Studies have reported that peripheral neuropathy (Abdissa, Adugna, et al, 2020 ; Adem et al, 2020 ; Mariam et al, 2017 ; Woldemariam et al, 2020 ), poor foot self‐care behaviours (Mariam et al, 2017 ; Tola et al, 2021 ; Tolossa et al, 2020 ; Woldemariam et al, 2020 ) overweight and obesity (Adem et al, 2020 ; Mariam et al, 2017 ; Tola et al, 2021 ; Tolossa et al, 2020 ), taking insulin alone (Tola et al, 2021 ; Woldemariam et al, 2020 ), rural residence (Mariam et al, 2017 ; Tolossa et al, 2020 ), delayed DM follow‐up, history of infection and hypertension (Tola et al, 2021 ), and presence of foot callus, longer duration of DM and advancing age (Tolossa et al, 2020 ) are positively associated with DFU. In addition, a studies have shown that retinopathy, nephropathy, poor glycaemic control, smoking and height are positively associated with DFU (Banik et al, 2020 ; Rossboth et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by a case-control study done in Tikur Anbessa Specialized Hospital in Ethiopia patients who take a combination of oral hypoglycemic medication and insulin were 89% less likely to develop diabetic foot ulcers than patients who took insulin only. 21 This study showed that patients who lived with DM for more than 5 years were 2.28 times more likely develop diabetic foot ulcer than patients who lived with DM for less than 5 years (AOR=2.28, 95% CI=3.04, 17.69). This is supported by a study done in Felege Hiwot referral hospital at Bahir Dar, Ethiopia that revealed that patients who follow for 6-10 years were 2.44 times more likely to develop DM complications than those who are living with DM for <5 years respectively.…”
Section: Discussionmentioning
confidence: 67%
“…20 In another case-control study done in Tikur Anbessa Hospital, Ethiopia patients with peripheral neuropathy were 7.56 times more likely to develop foot ulcers. 21 A possible explanation is that in patients with peripheral neuropathy, the sensitivity and loss of vibration sensation significantly increases the risk of trauma, and the patient is unaware of the onset of sores/ulcers. This study showed that patients with diabetes who take only oral hypoglycemic medication were 3.2 times more likely to develop diabetic foot ulcers than those patients who take a combination of oral hypoglycemic medication and insulin.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that the instrument tool was easy and uncomplicated to use as well as having a manual provided. The reliability depends primarily on good standardization (Woldemariam et al, 2020) and instructions being easy to understand (Akila et al, 2021). Another possible explanation is that the risk factors were objective which influenced reliable scores or outcomes.…”
Section: Discussionmentioning
confidence: 99%